Modal Sosial Dalam Mewujudkan Kebersihan Lingkungan Bantaran Sungai - Salsha Dwi Agustina; Indah Meitasari (Jurnal Penelitian Pendidikan Geografi, 2023)
One of the problems faced by developed and developing countries in the world, such as Indonesia, is waste. Garbage cannot be considered as a matter of environmental hygiene alone, but can be the root of social problems. This study aims to: 1) describe social capital that can be realized for environmental cleanliness; 2) describes the social capital that exists among residents in the form of cooperation and social networks; and 3) describe the values or norms, as well as the beliefs contained in the social network owned by the community of RW 03 Kelurahan Cimpaeun. This study uses qualitative methods with field observations. The results of the study show that: 1) there are norms in society that apply in maintaining environmental cleanliness where the people of RW 03 Cimpaeun Village have carried out activities in environmental cleanliness with good cooperation and are also structured through social capital of the community; 2) there are several community social sanctions; and 3) The trust of RW 03 Cimpaeun Village residents towards environmental cleaning activities has a positive response from the community in environmental cleaning activities.